Eosinophilic Esophagitis and Microbiota: State of the Art - Mennini, Maurizio; Tambucci, Renato; Riccardi, Carla; Rea, Francesca; De Angelis, Paola; Fiocchi, Alessandro; Assa’ad, Amal (Frontiers in Immunology, 2021)
Eosinophilic esophagitis (EoE) is a chronic, food-triggered, immune-mediated disease of the oesophagus, clinically characterized by symptoms referred to oesophagal dysfunction, and histologically defined by an eosinophil productive inflammation of the oesophagal mucosa, among other cell types. The involvement of an adaptive Th2-type response to food antigens in EoE was known since 2000; several cytokines and chemokines promote food-specific responses, during which local production of IgE, but also IgG4 derived from plasma cells in lamina propria of oesophagal mucosa might play an important role. Evidence pointing towards a possible role for the innate immunity in EoE has arisen recently. Together, this evidence gives rise to a potential role that the innate immune system in general, and also the microbial pattern recognition receptors (PRRs) might play in EoE pathogenesis. Among PRRs, Toll-like receptors (TLRs) are type-I transmembrane receptors expressed both on epithelial and lamina propria cells with the capacity to distinguish between pathogen and commensal microbes. As TLRs in the different intestinal epithelia represent the primary mechanism of epithelial recognition of bacteria, this evidence underlines that oesophagal TLR-dependent signalling pathways in EoE support the potential implication of microbiota and the innate immune system in the pathogenesis of this disease. The oesophagal mucosa hosts a resident microbiota, although in a smaller population as compared with other districts of the gastrointestinal tract. Few studies have focused on the composition of the microbiota of the normal oesophagus alone. Still, additional information has come from studies investigating the oesophagal microbiota in disease and including healthy patients as controls. Our review aims to describe all the evidence on the oesophagal and intestinal microbiota in patients with EoE to identify the specific features of dysbiosis in this condition.